Women in Educational Leadership: Realities and Challenges - Pant, Yashodhara; Shiwakoti, Rabindra (Nepal Journal of Multidisciplinary Research, 2025)
Background: The discourse on school leadership is evolving as women increasingly assume leadership roles across various sectors globally. This shift underscores the importance of hiring and empowering women in key educational leadership positions, given the potential advantages of such representation. Despite expanded opportunities, women often navigate these roles in an unplanned, spontaneous manner, highlighting the need to examine their experiences and challenges. Objective: This study explores how women capitalize on emerging opportunities to lead in educational institutions, focusing on their personal experiences, challenges, and strategies for overcoming barriers. The research aims to provide insights into the unique contributions of female leaders and identify support systems to enhance their impact in school leadership. Methods: A qualitative research design was employed, utilizing semi-structured interviews with 15 female school leaders across various educational levels. The study is framed through a critical feminist perspective, which informs the analysis of gender dynamics in educational leadership. The interviews centered on participants' career trajectories, institutional barriers, and leadership strategies. Findings: Key themes emerged, including the influence of career choices, societal and institutional barriers, and adaptive leadership strategies employed by women. The study reveals that educational leadership remains a complex and gendered issue, with significant implications for policy and practice. Female leaders often navigate systemic challenges while leveraging collaborative and transformative leadership approaches. Conclusion: This study contributes a critical feminist lens to the discourse on women in educational leadership, offering a framework for stakeholders to understand and support female leaders. The findings highlight the need for targeted policies and institutional changes to foster gender equity in leadership roles. Novelty: The novelty of this work lies in its emphasis on the unplanned nature of women’s leadership trajectories and their adaptive strategies, providing actionable insights for advancing women in school leadership.